SYSTEMATIC REVIEW OF THE EFFICIENCY OF TELEMEDICINE DURING THE COVID-19 PANDEMIC - Yuniasih, Dewi; Mansur, Auliya Azisah; Dewantari, Aulia Nissa; Dewantari, Aulia Yasmin; Annisa, Ika Nur; Susilawati, Okti (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
COVID-19 is a world health problem that has caused significant changes in the health care system. During the COVID-19 pandemic, some efforts are needed to reduce the spread of the. Telemedicine, as a remote technology, is one of the effective options for use in the healthcare system today. This study aims to explore the efficiency of using telemedicine as one of the facilities in the context of controlling COVID-19. This systematic review research uses 4 databases: PubMed, ScienceDirect, ProQuest, and Wiley. The keywords used are